Perceptions of Fishermen Society on Insurance Assistance Program for Fishermen (IAPF) of Panai Hilir Subdistrict of Labuhanbatu Regency of North Sumatra Province. - Nurwono Yudo; Kusai Kusai; Darwis Darwis (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbtractThis study aims to analyze the Perceptions of Fishermen Society Against Insurance Assistance Program for Fishermen (IAPF) Panai Hilir Subdistrict Labuhanbatu District of North Sumatra Province. Population in this research is fisherman society which follow program of Insurance assistance Premium for Fisherman (IAPF) in District of Panai Hilir Regency of Labuhanbatu of North Sumatera Province with 25 respondents. Data collection techniques used were questionnaires.The results of this study indicate that the mechanism of implementation of insurance for fishermen in Panai Hilir Subdistricthas been in accordance with applicable legislation and technical guidelines and can be groupedinto the socialization stage, followed by the submission of insurance participants and the stage of insurance benefit claims. The results of this study also indicate that the perception of the fishermen community against the insurance program has a pretty good value with a total score of 2.013 which means that insurance is important to ensure the activities of fishermen in doing business so that fishermen will get protection, comfort and security in work. Keywords: Insurance, Mechanism, Perception, Fisherman Society.